Prediksi Kinerja Steamflood Dengan Metode Myhill-Stegemeier dan Gomaa di Area R Duri Steamflood (DSF) - Rycha Melysa (Universitas Islam Riau (UIR) Press, 2016)
Steamflood constitutes one of method Enhanced Oil Recovery (EOR) by injected steam with quality and particular flow rate kontinyu into reservoir. Its aim is increase oil mobility at reservoir by downs viscosity to produced passes through producer. Before does simulation exhaustively, there is it is better does to predict performance a steamflood's reservoir by analytic simple one. This studies compares two simple methods in prediction steamflood's reservoir performance by use of data historical on area R Duri Steamflood (DSF). Gomaa's method utilizes many graph have already at previous generalizing but just applies on field with given characteristic limitation. Then Myhill Stegemeier modifies equation that made by Mandl and Volek to interpose that displacement form in reservoir is frontal displacement one dimension yawns to oil. Both of that method have excess and its lack each. Compares two simple methods in predicting reservoir performance steamflood using historical data on the area